PENGARUH PELATIHAN TEKNOLOGI PESTISIDA LIMBAH TEMBAKAU TERHADAP PERILAKU PETANI - Pingkan Aditiawati; Mia Rosmiati; Dadang Sumardi (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2015)
The purpose of the training is to socialize and provide comprehension to farmers about technologyinnovation of botanical pesticide from tobacco waste. Farmer- behavior change is expected to lead tofarmers’ desire to apply technological innovation of botanical pesticide. This research useddescriptive method. Determination of respondent is conducted by a census of all the farmers whoattended training on botanical pesticide technology (20 respondents). Indicators of farmer- behaviorchanges including cognitive, affective, and psychomotor about the benefits, how to make and apply thebotanical pesticide. The indicators are measured using a Likert scale. Data were analyzed usingdescriptive statistics. The results showed that the training of botanical pesticide technology has a goodinfluence on the behavior of farmers.